2007
DOI: 10.1053/j.gastro.2007.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Transcription Factor Activation in Helicobacter pylori–Infected Mongolian Gerbils

Abstract: Background & Aims-Helicobacter pylori interact with epithelial cells resulting in activation of cellular signaling pathways leading to an inflammatory response. The pattern and timing of transcription factor activation in H pylori-infected gastric mucosa remain unclear. We investigated the roles of transcription factors in the gastric mucosa of H pylori-infected gerbils over the course of the infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 39 publications
(53 reference statements)
2
32
2
1
Order By: Relevance
“…The attenuation of this FRET with the inhibition of ERK activity that we detected indicates that the close approximation of the pc-Fos⅐c-Jun dimer depends on phosphorylation of ERK. Several studies have assessed potential AP-1 constituents in the response to H. pylori (27)(28)(29)(30)(31)(32), but in contrast to our study, they have not demonstrated the composition of the complex, the physical interaction of the components, the involvement of pc-Fos, or the role of AP-1 in apoptosis.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…The attenuation of this FRET with the inhibition of ERK activity that we detected indicates that the close approximation of the pc-Fos⅐c-Jun dimer depends on phosphorylation of ERK. Several studies have assessed potential AP-1 constituents in the response to H. pylori (27)(28)(29)(30)(31)(32), but in contrast to our study, they have not demonstrated the composition of the complex, the physical interaction of the components, the involvement of pc-Fos, or the role of AP-1 in apoptosis.…”
Section: Discussioncontrasting
confidence: 80%
“…In contrast, we found that inhibition of p38 had no effect and that interference with c-Fos phosphorylation with a dominant-negative plasmid completely attenuated the induction of apoptosis. Similarly, in studies in gastric epithelial cells (27)(28)(29)(30), the role of pc-Fos in AP-1 complex formation has not been assessed, and p38 as well as JNK have been implicated in the cytokine response, in contrast to our results in macrophages. Further, the role of pERK or AP-1 has not been previously studied in the setting of H. pylori-induced expression of c-Myc, ODC, or apoptosis in either macrophages or epithelial cells.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…The oipA gene encodes an extracellular inflammatory protein that is considered as a virulence factor for H pylori (Kudo et al, 2007). It is found that oipA gene is present in samples from stomach of significant percentage of patients with gastritis and gastric ulcers (Salih et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…IL1B is a powerful pro-inflammatory cytokine that activates different transcription factors [19], some of which are also activated by H. pylori infection [20,21]. One of the IL1B-activated transcription factors is CCAAT/enhancer-binding protein beta (C/EBPb) [22].…”
Section: Introductionmentioning
confidence: 99%